PUBLIC INITIATIVES AS A FACTOR OF SOCIAL SELF-ORGANIZATION AND A SIGNIFICANT MECHANISM OF SOCIAL SERVICES PROVISION - Kosukhina , K. V. (Theory and Practice of Public Administration, 2021)
The article is devoted to the analysis of the development of public initiatives in Ukraine, as well as their role in building a dialogue between the government and civil society. The connection of the public initiative with the provision of social services is considered. The interaction of civil society institutions with public authorities is determined.The problem of the relationship between civil society and the state is one of the key in the development of democracy. Civil society can develop qualitatively only through the proper functioning of voluntary social institutions. Today in Ukraine there is an urgent need to effectively combine the efforts of government and citizens and introduce new mechanisms to involve the public in the process of providing social services. This determines the purpose of the article – theoretical and methodological justification of public initiatives as a factor of self-organization of society and the mechanism of providing social services. In accordance with the set goal, the following tasks are formulated: to reveal the meaning of the concept of “public initiative” and “social service”, as well as to determine the mechanisms of interaction of civil society institutions with public administration bodies.